Identification of New Lactone Derivatives Isolated from Trichoderma sp., An Endophytic Fungus of Brotowali (Tinaspora crispa) - . ELFITA; . MUNAWAR; . MUHARNI; MASTUR ADHY SUDRAJAT (HAYATI Journal of Biosciences, 2014)
Endophytic fungi is a rich source of novel organic compounds with interesting biological activities and a high level of structural diversity. As a part of our systematic search for new bioactive lead structures and specific profiles from endophytic fungi, an endophytic fungus was isolated from roots of brotowali (Tinaspora crispa), an important medicinal plant. Colonial morphological trait and microscopic observation revealed that the endophytic fungus was Trichoderma sp. The pure fungal strain was cultivated on 7 L Potatos Dextose Broth (PDB) medium under room temperature  (no shaking) for 8 weeks. The ethyl acetate were added to cultur medium and left overnight to stop cell growth. The culture filtrates were collected and extracted with EtOAc and then taken to evaporation. Two new lactone derivatives, 5-hydroxy-4-hydroxymethyl-2H-pyran-2-one (1) and (5-hydroxy-2-oxo-2H pyran-4-yl) methyl acetate (2) were obtained from the EtOAc extracts of Trichoderma sp. Their structures were determined on the basic of spectroscopic methods including UV, IR, 1H-NMR, 13C-NMR,  HMQC, and HMBC.